USING THINK PAIR SHARE TO IMPROVE STUEDNTâ€™S ACTIVENESS IN TEACHING LERANING PROCESS - Salimah, Salimah; Ikhsanudin, Ikhsanudin; Supardi, Iwan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe purpose of this research is to investigate how well Think Pair Share technique can improve students activeness to the ten grade students of SMA Bina Mandiri Teluk Pakedai. The research conducted this project in order to solve the problems encountered in the classroom.Since it is to improve students activeness in teaching learning process. The appropriate technique that was applied in this research is a classroom action research with the cycle of planning, acting, observing, and reflecting. The participant of this research is the students in ten grade students of SMA Bina Mandiri Teluk Pakedai in academic 2017/2018, which consist of 15 students.After collecting the data, the writer found out that the Think Pair Share technique was useful to students activeness. Based on students abservation, the researcher discovered a good mark that was shown by students activeness from cycle to cycle was increases. The students activeness in the first cycle was moderate. The students activeness in the second cycle was good.The finding of the classroom action research were satisfying. All the indicator of success had been fulfilled. The students activeness was increased and teaching learning become better. Think Pair Share helps students to improving the activeness.Â Key words: Think Pair Share, Activeness